Evaluation of health behaviour of patients with arterial hypertension and its selected predispositions - Kropornicka, Beata; Dąbrowska, Joanna; Baczewska, Bożena; Krzyżanowska, Ewa; Łuczyk, Robert Jan (Journal of Education, Health and Sport, 2019)
Introduction. Arterial hypertension is a valid modifiable risk factor of the circulatory system diseases. The aim of this study was to evaluate the health behaviour of patients with arterial hypertension and its selected predispositions. Material and methods. The study was conducted in the Cardiology Department of the Clinical Hospital no. 4 in Lublin, the Cardiology Department of no. 1 Military Hospital in Lublin and Cardiology Department of Public Clinical Hospital no. 1 in Lublin. In the study the diagnostic survey of the Inventory of Health Behaviour (Inwentarz Zachowań Zdrowotnych, IZZ) by Juczynski Z. was used. The patients’ body mass and height BMI (Body Mass Index) for each of them was calculated. Results of the study. The patients with arterial hypertension most often declare a high level of health behaviour. The research subjects show more beneficial health behaviour in the areas of preventative actions, health practices and positive mental attitude than in the healthy eating habits domain. Conclusions. BMI index does not differentiate the level of healthy eating practices and preventative actions. However, the level of health practices is significantly higher among people diagnosed with excess weight and obesity. It is an optimistic attitude to life that influences health behaviour positively rather than realistic and pessimistic attitude. The placement of the health assessment responsibility is linked to the mental attitude of the studied patients.